Endovascular Thrombectomy for Anterior Circulation Large Vessel Occlusion Stroke: An Evolution of Trials - Starikova, Natalia; Räty, Silja; Strbian, Daniel; Kaiser, Daniel P. O.; Gerber, Johannes C.; Huo, Xiaochuan; Qiu, Zhongming; Chen, Hui-Sheng; Kaesmacher, Johannes; Pallesen, Lars-Peder; Barlinn, Kristian; Sun, Dapeng; Abdalkader, Mohamad; Nguyen, Thanh N.; Nagel, Simon; Miao, Zhongrong; Puetz, Volker (Seminars in Neurology, 2023)
The last decade's progress in demonstrating the clinical benefit of endovascular thrombectomy (EVT) in patients with large vessel occlusion stroke has transformed the paradigm of care for these patients. This review presents the milestones in implementing EVT as standard of care, demonstrates the current state of evidence, provides guidance for identifying the candidate patient for EVT, and highlights unsolved and controversial issues. Ongoing trials investigate broadening of EVT indications for patients who present with large core infarction, adjunctive intra-arterial thrombolysis, medium vessel occlusion, low NIHSS, and tandem occlusion.
Keywords: anterior circulation LVO stroke; mechanical thrombectomy; medium vessel occlusion; large ischemic core; large infarct; outcome; clinical trial